Correction to: Effects of Moisture-Induced Crystallization on the Aerosol Performance of Spray Dried Amorphous Ciprofloxacin Powder Formulations - Shetty, N.; Zeng, L.; Mangal, S.; Nie, H.; Rowles, Matthew; Guo, R.; Han, Y.; Park, J.; Zhou, Q. (AAPS, 2018)
Page 4, right column, under section heading “In-Vitro Aerosol Performance”, line 11. “ < 4 kPa (approximately 3.2 kPa at 100 L/min)” should be changed to “approximately 4 kPa at 100 L/min”.